Efficacy of antiviral prophylaxis in HBsAg‐negative, anti‐HBc positive patients undergoing hematopoietic stem cell transplantation. (19th June 2015) - Yoo, Jeong‐Ju; Cho, Eun Ju; Cho, Young Youn; Lee, Minjong; Lee, Dong Hyeon; Cho, Yuri; Lee, Jeong‐Hoon; Yu, Su Jong; Yoon, Sung‐Soo; Yoon, Jung‐Hwan; Kim, Yoon Jun
Abstract: Background & Aims: Hepatitis B virus (HBV) reactivation can occur in persons who are hepatitis B surface antigen (HBsAg)‐negative but hepatitis B core antibody (anti‐HBc) positive, especially following hematopoietic stem cell transplantation (HSCT). However, evidence supporting the routine use of prophylactic antiviral agents for such patients is scarce. The aim of this study was to compare the frequency of HBV reactivation between prophylactic and non‐prophylactic groups in patients who underwent HSCT. Methods: This retrospective cohort study included 315 HBsAg‐negative, anti‐HBc positive patients who received autologous or allogenic stem cell transplantation from January 2008 to December 2013. Patients were categorized into prophylactic and non‐prophylactic groups. The primary endpoint was the incidence of HBV reactivation. Results: Median follow‐up duration was 21.4 months. Antiviral prophylaxis was not given to 219 patients, and 96 received prophylaxis. The median duration of prophylaxis was 7.0 months. HBV reactivated in 12 patients (prophylactic group, 4; non‐prophylactic group, 8). The median time to reactivation was 20.5 months after starting chemotherapy. All patients who reactivated were promptly and successfully treated with rescue antiviral agents. The risk of reactivation did not differ between prophylactic and non‐prophylactic groups ( P = 0.061) but was increased significantly by the allogenic type of HSCT and the loss of recipient's antibodies against HBsAg (anti‐HBs). Conclusions: Short‐term antiviral prophylaxis appears insufficient to decrease the risk of HBV reactivation. Therefore, either prophylaxis longer than 24 months or careful monitoring of HBV DNA combined with on‐demand antiviral treatment may prove more effective than the routine short‐term prophylaxis given to these patients.